INVESTIGATION OF SOME MECHANICAL PROPERTIES OF PINE WOOD UNDER A RIGID TEST MODE - Homon, П. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
Domestic and foreign works on the study of physical and mechanical properties of deciduous and coniferous wood by axial compression along the fibers are analyzed in detail. A method of experimental studies of pine wood with a single short-term compressive load along the fibers is proposed. It allows to test such materials under a rigid mode (by increasing displacements). It is established that such experimental researches should be carried out on modern servohydraulic or electromechanical testing machines and presses. Experimental studies of pine wood materials with a cross section of 30×30×120 mm with a standard humidity of 12 % under a rigid test mode (by increasing displacements) by axial compression along the fibers on a modern servo-hydraulic test machine STM-100. Based on the experiment, complete diagrams of the deformation “stress σс – relative deformations uc” of pine wood were constructed. The average relative critical deformations of pine wood uc, 0, d and their corresponding maximum stresses fc, 0, d were experimentally established. The residual relative deformations of such materials uc, fin and their corresponding stresses are also determined. The average values of the obtained indicators were established, in particular the average value of critical deformations was uc, 0, d = 0,00342; maximum stresses fc, 0, d = 39.5 MPa; residual relative deformations uc, fin = 0,301 It is confirmed that the diagrams of wood deformation «stress σc – relative deformations uc» have ascending and descending branches, as well as have characteristic points in certain areas. With the help of such complete mechanical characteristics it is possible to determine the actual stress-strain state of reinforced and non-reinforced wooden elements and structures and to perform appropriate calculations.